STUDY OF STUDENT SATISFACTION LEVEL OF TEACHER PEDAGOGICAL ABILITY IN LEARNING IMPLEMENTATION - Husna, Hafizul; Rohendi, Dedi; Mubarak, Ibnu; Sutia, Iyep; sriyono, sriyono; Kuntadi, Iwa (Journal of Mechanical Engineering Education, 2020)
This4study4aims6to4determine6how7much7the7level_of_student_satisfaction_with_the_teachers ability to^carry out learning. This is motivated^by the fact that there are still many students scores^that have not reached the graduation^level which is caused by*dissatisfaction with the services*provided by the teacher when carrying^out learning.The method-used in this study is a quantitative^method with a descriptive approach and a^survey^research^design^with^a^population^of^all students^of^class^XII^TKR^SMKN^6^Bandung^and a sample of 65 students. Data obtained^using a questionnaire distributed-to students using google-form. The result of the^expert judgment indicate that the research^instrument is valid for use. The result*of this study indicate the percentage^of satisfaction of 56,7% is in the*unsatisfactory category. This shows^that there is still a lack of teacher_pedagogical ability in implementing_learning.So, it can be concluded that satudets are not_satisfied with the pedagogical^ability of the teacher*which*results*in*many*students who do not reach the passing level*in productive subject.